Improving The Performance Of Dc Motor Drive Application For Dc-Dc Converter By Using Resistance Compression Network (International Journal of Engineering and Computer Science, 2015)
In this paper improve the performance of DC motor by the resistance compression network. The output DC supply is dependence upon number of transformer winding ratio. If the DC input side voltage is two times of the output side voltage. The RCN maintains desired current waveforms over a wide range of voltage operating conditions. HIGH-voltage-pick up dc/dc converters are found in a mixed bag of utilizations [1]–[4]. For instance, to associate photovoltaic boards to the lattice, interface hardware is required. A few architectures for this reason consolidate dc/dc converters to support voltage of individual photovoltaic boards to a high dc-join voltage, with take after on gadgets for changing over dc to air conditioning (e.g., see, [5] and [6]). The progression up dc/dc converter is a discriminating piece of this framework, and must work effectively for an extensive voltage venture up and for a wide voltage range (e.g., at the converter information and/or yield contingent on the framework). Moreover, to be minimal, it must work at high exchanging frequencies. In ordinary hard-exchanged force converters, the cover of current and voltage is extensive amid exchanging, bringing about huge force misfortune, particularly at high frequencies. We implementing torque and speed characteristics are performed by the Resistance Compression Network (RCN). The validated results are verified by the MATLAB/SIMULINK Software